Decline in the strength of genetic controls on aspen environmental responses from seasonal to century‐long phenomena. Issue 9 (25th September 2019) - Drobyshev, I.; Picq, S.; Ganivet, E.; Tremblay, F.; Bergeron, Y.
Abstract: Understanding intra‐specific variation in climate sensitivity could improve the prediction of tree responses to climate change. We attempted to identify the degree of genetic control of tree phenology and growth of trembling aspen ( Populus tremuloides Mchx.) in a natural stand of this species in northwestern Quebec. We mapped and genotyped 556 aspen trees growing within the plot, using seven nuclear microsatellite loci for clone identification. We selected 13 clones ( n of trees per clone >5, in total 350 trees) and evaluated the explanatory power of clone identity in (a) variability of spring leaf phenology and (b) short‐ and long‐term growth responses. The clone's identity explained 43% of the variability in spring leaf phenology, between 18% and 20% of variability in response to monthly climate variables significantly affecting growth, between 8% and 26% of growth response to insect outbreaks, and 12% in the long‐term growth rates. Strong clonal control of aspen phenology and moderate control of growth responses to monthly weather do not result in an equally large impact on long‐term growth rates. The result suggests an important role of environmental extremes and within community interactions as factors averaging aspen growth performance at the stand level.